Synthesis of HAp/CS-SA composite for effective removal of highly toxic dyes in aqueous solution. (October 2022) - Sathiyavimal, Selvam; Vasantharaj, Seerangaraj; Kaliannan, Thamaraiselvi; Chinnathambi, Arunachalam; Ali Alharbi, Sulaiman; Krishnan, Ramakrishnan; Brindhadevi, Kathirvel; Lan Chi, Nguyen Thuy; Pugazhendhi, Arivalagan
Abstract: Textile industry is the major backbone of economy of the developing countries. The major problems associated in the textile factories are release of undesired dye effluents, which is a potential pollution risk for human health as well as the environmental aquatic system. The objective of this study was fabrication of a novel composite to treat textile industry effluents in an ecofriendly manner. In this context, hydroxyapatite (HAp) was derived from the mussel shell biowaste and fabricated with chitosan-sodium alginate through the in-situ method. The prepared HAp/CS-SA composite was physicochemically characterized by using Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Field emission scanning electron microscopy with energy dispersive X-ray spectroscopy (FESEM-EDX) and High Resolution-Transmission Electron Microscope (HR-TEM). The photocatalytic activity of the HAp/CS-SA composite was evaluated by using Congo red (CR), Malachite green (MG) and Methylene blue (MB) as model dyes for degradation in aqueous solutions under solar irradiation. The degradation rate was recorded as CR (88%), MG (81%) and MB (93%) respectively within 75 min of irradiation. The degraded end products were subjected to toxicity assessment by evaluating the phytotoxicity on seed germination of Vigna radiata plant in pot study. The degraded end products were also tested for toxic inhibition of E. coli and P. aeruginosa by agar well diffusion method. The prepared HAp/CS-SA composite had an enhanced photocatalytic activity due to the presence of natural biopolymers and their biological properties. HAp/CS-SA composite showed potential dye degradation properties and it could be effective for dye removal from industrial wastewaters. Highlights: Synthesis of HAp derived from mussel shell and HAp/CS-SA composite prepared by In situ method. HAp/CS-SA composite preparation is simple, low cost effective and environmentally-friendly. HAp/CS-SA composite has microporous and smooth fibrous structure to enhancing potential adsorption properties. Dyes degraded end products very less toxic effective to aquatic environment. Phytotoxicity and microbial toxicity studies were examined in this study.